Pengembangan Flashcard Berbasis Visual Thinking untuk Pembelajaran Kosakata Benda - M Iqbal Arrosyad; Zonalisa Fhatri (LINGUISTIK MIKRO, MAKRO DAN SASTRA, 2026)
This study was motivated by elementary students' limited mastery of object vocabulary and the lack of engaging learning media that suit learners' characteristics. The main objective of this study was to develop a visual thinking-based flashcard that is feasible for object vocabulary learning. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the stages of analysis, design, development, validation, and practicality testing. The study was conducted at SD Negeri 1 Pangkalpinang involving two validators and nine first-grade students. Data were collected through validation and practicality questionnaires. The results showed that the developed media obtained a validity score of 92.5% from the media expert and 92.5% from the material expert, both categorized as highly valid. The practicality test yielded a score of 94%, categorized as highly practical. Therefore, the visual thinking-based flashcard is feasible for use in object vocabulary learning at the elementary school level.